2010
DOI: 10.1007/s11325-010-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

Spousal involvement in CPAP adherence among patients with obstructive sleep apnea

Abstract: Introduction: Little is known about the impact of spousal involvement on continuous positive airway pressure (CPAP) adherence. The aim of this study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 73 publications
1
57
0
1
Order By: Relevance
“…Social factors such as socioeconomic status, social support, and partner involvement have been shown in some studies to affect adherence, although not in a simple manner. 42,45,53 Similarly, psychological factors have also been shown to predict adherence in many studies, [18][19][20] although not in all. 47,49 Most of the current literature focuses on the use of psychological interventions to promote CPAP usage (CBT, 54 motivational interviewing 55 ), but these are time and resource intensive, so that identifying who would or would not benefit from these interventions may be useful.…”
Section: 49mentioning
confidence: 99%
“…Social factors such as socioeconomic status, social support, and partner involvement have been shown in some studies to affect adherence, although not in a simple manner. 42,45,53 Similarly, psychological factors have also been shown to predict adherence in many studies, [18][19][20] although not in all. 47,49 Most of the current literature focuses on the use of psychological interventions to promote CPAP usage (CBT, 54 motivational interviewing 55 ), but these are time and resource intensive, so that identifying who would or would not benefit from these interventions may be useful.…”
Section: 49mentioning
confidence: 99%
“…The symptoms of OSA, including snoring, daytime sleepiness, and depressed mood, affect both patient and partner quality of life (Doherty et al 2003;Reishtein et al 2006;Cartwright 2008;Cartwright and Knight 1987;Baron et al 2009). In male participants, relationship conflict was associated with poorer adherence and collaborative involvement from the spouse was associated with higher adherence (Baron et al 2009(Baron et al , 2011. Results of this study cannot address gender differences per se; but, we can compare magnitude of correlations between studies.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that the women who did not provide responses to this question either did not experience unhelpful spousal involvement or were reluctant to report it. Our previous study of spousal involvement in men utilized a written survey and found that 57% of male patients reported their spouse attempted to scare them into using CPAP, which is typically viewed as a negative tactic (Baron et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Moreover, there are data to suggest that social support has a favorable effect on promoting CPAP adherence. [6][7][8][9][10] ans receiving CPAP therapy for OSA. Additional objective was to obtain preliminary data on the effect of PBS on CPAP adherence, vigilance, patient activation, and self-efficacy in veterans receiving CPAP therapy for OSA.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%